Most serious public corruption crimes: A review of Section 41 of the Peruvian Constitution - Vílchez Chinchayán, Ronald (2023)
This paper analyzes a criminal policy measure to fight against public corruption: non-applicability of the statute of limitations to the most serious crimes against Public Administration. The author focuses on the analysis of the use of this measure, as well as the disadvantages and problems that its implementation raises from both scholar doctrine and enforcement perspectives. Finally, the author makes an alternative proposal for the implementation of said constitutional provision.